{Linguistic translation and validation of the Menopause-specific Quality of Life (MENQOL) questionnaire in Greek menopausal women.} - Papadima, Evgenia-Ioanna; Boutsiadis, Anastasios; Soldatou, Alexandra; Ivanidou, Sofia; Vassilakou, Tonia; Michala, Lina (Menopause (New York, N.Y.), 2020)
OBJECTIVE: The objective of this study was to translate the Menopause-specific Quality of Life (MENQOL) questionnaire in Greek and validate it for usage in the Greek population both in written and electronic form. METHODS: The original English questionnaire MENQOL with 1-month recall period was translated by our team. According to instructions by Mapi Research Trust, the questionnaire was forward and back-translated, followed by patient testing and proofreading. Then it was transcripted electronically. Validation was performed with the following tests: internal consistency (reliability), stability (test-retest reliability) with Cronbach's alpha correlations, independent and paired t tests, and Pearson's correlation coefficients. RESULTS: A total of 105 women, the majority recently menopausal, participated in the study. Internal consistency using the Cronbach's alpha showed high reliability ranging between 0.833 (physical domain) and 0.896 (vasomotor domain) for the written, and 0.720 (physical domain) and 0.868 (vasomotor domain) for the online form. Test-retest reliability was also high for both forms. The sexual domain of MENQOL had the higher mean, indicating the highest impact on quality of life (3.80 ± 2.35). CONCLUSIONS: The Greek version of MENQOL is a reliable instrument for evaluating menopausal women. Availability of an online form will allow wider dissemination of the questionnaire. Further use of the questionnaire in Greece may lead to better understanding of the bothersome symptoms of menopause; a prerequisite to develop intervention studies for amelioration of quality of life.